WHAT CREATES TOURIST SATISFACTION IN PRAMBANAN TEMPLE? - Rohman, Isnanda Zainur (KINERJA, 2021)
AbstractTourism is an industry which has a potential significant role in economic growth around the world. Indonesia is a country which also prepares for a world class tourism industry. In this country, there is a UNESCO world heritage site named Prambanan temple located in Yogyakarta. The purpose of this research is to get the antecedents of tourist satisfaction in Prambanan temple. The level of tourist satisfaction is an important thing for tourist attraction marketers. It is claimed that a successful tourist attraction is a place which gives more satisfaction for its vistiors. There were 500 respondents filling the questionnaires of this study. The data were processed by SPSS and AMOS program. Descriptive statistics, validity, reliability, model fit, and regression analyses were run to prove the hypotheses. The result shows that perceived value, perceived quality, and destination image determine the level of tourist satisfaction. There are two kinds of implications from this research. Theoretically, this research strengthens the findings from the previous researches. Practically, this research gives some perspectives for tourist destination managers to create a better marketing strategy by giving more attention to perceived value, perceived quality, and destination image. This research also gives several suggestions for the next researches.Â Keywords: tourism, marketing, tourist satisfaction, Prambanan temple